Neurological Complications of Measles in Children: A Systematic Review - Norlaila Sofia; Asy-Syifa Nashriyah; Noor Adha Aprilea; Tri Tunggal (Optimal Midwife Journal, 2025)
Measles remains a major global health issue, including in Indonesia, with more than 10,600 cases reported in 2023 and approximately 3,400 cases until August 2025. Although most cases are self-limiting, neurological complications such as encephalitis and Subacute Sclerosing Panencephalitis (SSPE) remain significant causes of morbidity and mortality in children. This review summarizes recent evidence on the clinical characteristics, diagnostic approaches, and management of measles encephalitis in children. A literature search was conducted using Publish or Perish with the query “measles encephalitis” AND (child OR children OR pediatric) across Scopus, PubMed, Semantic Scholar, and Google Scholar, covering the period 2015–2025. Selection followed PRISMA guidelines through identification, screening, eligibility, and inclusion. Of 157 articles identified, 13 met the criteria. Case reports comprised 69.2%. Diagnosis was most frequently based on cerebrospinal fluid (CSF) analysis and electroencephalography (EEG) (≥70%), followed by reverse transcriptase polymerase chain reaction (RT-PCR) (46.1%) and histopathology (15.4%). Acute encephalitis was described in 84.6% of articles with nearly 50% mortality. SSPE was reported in 53.8% with progressive and fatal outcomes. Cases in immunocompromised children and neonates (15.4% each) showed more aggressive progression. Only two articles discussed therapeutic interventions with inconsistent outcomes. Measles encephalitis in children remains a critical challenge due to high mortality and limited therapeutic options. This review summarizes the latest evidence on the clinical and diagnostic spectrum of measles encephalitis and highlights the urgent need for research on diagnostic biomarkers and innovative therapies in the future.